Panax ginseng (Korea Red Ginseng) repairs diabetic sensorineural damage through promotion of the nerve growth factor pathway in diabetic zebrafish - Nam, Youn Hee (J Ginseng Res, 2019)
BACKGROUND: Diabetic sensorineural damage is a complication of the sensory neural system, resulting from long-term hyperglycemia. Red ginseng (RG) has shown efficacy for treatment of various diseases, including diabetes mellitus; however, there is little research about its benefit for treating sensorineural damage. Therefore, we aim to evaluate RG efficacy in alloxan-induced diabetic neuromast (AIDN) zebrafish. METHODS: In this study, we developed and validated an AIDN zebrafish model. To assess RG effectiveness, we observed morphological changes in live neuromast zebrafish. Also, zebrafish has been observed to have an ultrastructure of hair-cell cilia under scanning electron microscopy. Thus, we recorded these physiological traits to assess hair cell function. Finally, we confirmed that RG promoted neuromast recovery via nerve growth factor signaling pathway markers. RESULTS: First, we established an AIDN zebrafish model. Using this model, we showed via live neuromast imaging that RG fostered recovery of sensorineural damage. Damaged hair cell cilia were recovered in AIDN zebrafish. Furthermore, RG rescued damaged hair cell function through cell membrane ion balance. CONCLUSION: Our data suggest that RG potentially facilitates recovery in AIDN zebrafish, and its mechanism seems to be promotion of the nerve growth factor pathway through increased expression of topomyosin receptor kinase A, transient receptor potential channel vanilloid subfamily type 1, and mitogen-activated protein kinase phosphorylation.